(untitled) (Swiss Medical Weekly, 2015)
The discovery of proprotein convertase subtilisin kexin 9 (PCSK9) has considerably changed the therapeutic options in the field of lipid management. PCSK9 reduces LDL receptor recycling, leading to a decrease of low-density lipoprotein cholesterol (LDL-C) receptors on the surface of hepatocytes and a subsequent increase of circulating LDL-C levels. In observational studies, the loss-of-function mutations of PCSK9 have been associated with a reduction of LDL-C levels and cardiovascular disease (CVD) events. In contrast, humans with high levels of PCSK9 have higher level of plasma LDL-C and significantly enhanced CVD risk during their lifetime, gain-of-function mutations on PCSK9 are, for instance, causatively associated with familial hypercholesterolaemia (FH). Inhibition of PCSK9 is therefore a promising therapeutic option for the lowering of LDL-C levels. The clinical development of human monoclonal antibodies against PCSK9 has progressed, with promising results reported from phase 2 clinical studies in patients with FH or intolerant to statin with LDL-C levels not on target levels. Phase I studies demonstrated safety and efficacy. In phase II, a 60%–70% reduction in LDL-C was observed, especially when subcutaneous injections were performed regularly every two weeks. No significant side effects were observed, with the exception of injection site reactions. Three large phase III programmes with the new anti PCSK9 antibodies are currently underway in patients with acute coronary syndrome (ACS) and LDL-C inadequately controlled by standard treatments. The main objective of these studies is to evaluate the effect of PCSK9 inhibition on the occurrence of CVD events in patients with ACS.